Psychometric Evaluation of the Chinese Recovering Quality of Life (ReQoL) Outcome Measure and Assessment of Health-Related Quality of Life During the COVID-19 Pandemic - Xu, Richard Huan; Keetharuth, Anju Devianee; Wang, Ling-ling; Cheung, Annie Wai-ling; Wong, Eliza Lai-yi (Frontiers in Psychology, 2021)
Objective The primary objective was to translate the Recovering Quality of Life (ReQoL) measures from English to traditional Chinese and assess their psychometric properties in Hong Kong (HK) Chinese population. The secondary objective was to investigate the mental health-related quality of life of this sample during the Coronavirus disease 2019 pandemic. Method ReQoL was translated to Traditional Chinese adhering to standard guideline recommended by the official distributors. Five hundred members of the general population were successfully recruited to participate in a telephone-based survey. The following psychometric properties of the ReQoL were evaluated: construct, convergent, and known-group validity and internal consistency and test-retest reliability. The item measurement invariance was assessed on the basis of differential item functioning (DIF). Multiple regression analysis was used to assess the relationship between respondents’ characteristics and mental HRQoL. Results Results of confirmatory factor analysis supported a two-factor structure of the ReQoL. The ReQoL showed significant correlations with the other mental health, quality of life, and well-being measures, which indicated a satisfactory convergent validity. Known-group validity confirmed that ReQoL is able to differentiate between people with different mental health status. The Cronbach’s alpha of 0.86 (0.91 and 0.76 for positive [PF] and negative [NF] factor, and McDonald’s omega of 0.89 (PF=0.94, NF=0.82) indicated the ReQoL has good reliability as well as test-retest reliability with an intraclass correlation coefficient of 0.75. Four items showed negligible DIF with respect to age. Respondents who were highly educated and without psychological problems reported a high ReQoL score. Conclusions Traditional Chinese ReQoL was shown to be a valid and reliable instrument to assess the recovery-focused quality of life in HK general population. Future studies are needed to appraise its psychometric properties in local people experiencing mental disorders.